The M&A Sucess Factors : beyond the financial monomania - Vacha, Robert; Poborský, František; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2019)
Mergers and acquisitions have been experiencing increasing importance in the global business world over the course of past decades. Research has shown that majority of M&A endeavors fail to fulfil the expectations and to create value. This thesis aims to bring more clarity into determinants of successful M&A. Building on the existing research as well as its own survey of M&A advisors across Europe, it asks:„What are the factors influencing the outcome/success of M&A? “In this context, success is defined as “Fulfilment of primary motives and/or overall satisfaction with the outcome of M&A”. Analysis of the responses based on the direction of influence and the level of consensus established on individual factors has identified areas of focus that could lead to increased performance of M&As. The results indicate that forward-looking approach with focus on envisioning the keen post-acquisition entity backed by due investigation of the target are to have positive impact on the outcome of M&As. Further positive influence was found in the alignment of managers’ and shareholders’ interests, either through long-term oriented KPIs or holding of a common stock. Further research is needed to identify other factors that influence performance of M&As and establish link between the primary motives of companies undergoing M&A and their results.
Vedoucí práce: František Poborský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses